Penerapan Strategi Pembelajaran Pada Mata Pelajaran Akidah Akhlak Di MtsS Miftahul Huda Desa Silikuan Hulu Kecamatan Ukui Kabupaten Pelalawan - Nurul Jannah Ramadhanty; Iswantir Iswantir; Wedra Aprison; Arifmiboy Arifmiboy (Lembaga Pengembangan Kinerja Dosen, 2023)
Learning strategies can be interpreted as an outline of a course or general patterns of activities carried out by an educator and students in the embodiment of teaching and learning activities to achieve the goals outlined. There are several problems found by researchers in research locations, especially in the learning process of Akidah Akhlak at MTsS Miftahul Huda Silikuan Hulu Village, Ukui District, namely, students are not able to directly absorb the material presented by the teacher, lack of enthusiasm of students in class when learning Akidah Akhlak which causes some students to not care about the material presented by the teacher, and the teacher's lack of understanding of the application of learning strategies which can be seen from the learning process the teacher only uses monotonous learning strategies so that it does not increase the learning enthusiasm of students in the classroom. This research includes qualitative research, the data collected is in the form of words and pictures, in this case it is explaining how teachers use learning strategies. Researchers collected data through interviews, documentation, and field notes. Data were analyzed in three stages, namely data reduction, data presentation, and data verification. Techniques for guaranteeing the validity of the data are source triangulation, technical triangulation, and time triangulation. Based on the results of the research that the researchers conducted, it can be concluded that: (1) The strategies used by the aqidah moral teachers in class VIII semester 2 of MTsS Miftahul Huda Siliuan Hulu Village, Ukui District, namely problem-based strategies, discovery learning strategies, and cooperative learning strategies (2) Steps -Steps for implementing learning strategies in the subject of Aqidah Akhlak a. Opening learning activities, b. Explain the competence to be achieved, c. Educators help students define organizing tasks. d. Educators and students arrange tasks together. e. Students collect information according to the problem being discussed. f. Educators supervise the course of learning activities g. The teacher gives an explanation of the material. (3) Obstacles faced in implementing the implementation of the learning strategy of aqidah morals at MTsS Miftahul Huda Silikuan Hulu Village, namely the lack of teacher preparation in implementing learning, for the learning process to be carried out suddenly.